Climate Change and Internal Migration in India: Response of the State, Market, and the Civil Society. Issue 2 (14th June 2013) - Jha, Anil Kumar
Abstract Climate change has become a major concern for the international community. Among its consequences, its impact on migration is the object of increasing attention from both policymakers and researchers. Yet knowledge in this field remains limited and fragmented. This article, therefore, provides an overview of the climate change–migration nexus in India. It investigates the key issues at stake, including the social and political context in which the topic emerged. It further investigates the responses of the state, market and the civil society. Two major interconnected arguments arise. The first regards the weight of environmental and climatic factors in migration and their relationship to other push or pull factors, whether of social, political, or economic nature. The second is about the political framework in which such migration flows should take place and the manner in which to treat the people who move in connection with environmental factors. The two issues are deeply intertwined, as the extent to which the environment determines migration is intimately connected to the status to be associated with the people concerned. The ISMW Act is an obsolete piece of legislation by the Government of India in this regard. Some of the work that civil society is doing—for instance, the move to issue migrants an ID, provide them with skills training, offer legal protection, and financial services—is highly scaleable. They are not unique to a specific geography; they are fairly universal solutions that can be taken to any geography and any group of migrants across the country. Of course, civil society is limited by its resources, its networks, and its ability to deliver. Therefore, it can partner well with governments to deliver these services.